Strategi Pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM) Dalam Meningkatkan Perekonomian Masyarakat Desa: Studi Kasus di Desa Cikamunding, Kecamatan Cilograng, Kabupaten Lebak, Banten - Syaechurodji Syaechurodji; Didit Haryadi; Rhifwan Aji Bimantoro Adriyanto (PT. Alahyan Publisher Sukabumi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the main drivers of the rural economy. However, MSMEs in Cikamunding Village, Cilograng District, Lebak Regency, Banten, still face various obstacles, such as limited managerial skills, conventional marketing, low digital literacy, and suboptimal business financial management. These conditions impact low competitiveness and business development. This community service activity aims to increase the capacity of MSMEs through outreach and mentoring on business development strategies, simple financial management, and the use of digital media as a marketing tool. The method used is a participatory approach with the stages of observation, needs identification, outreach, mentoring, and monitoring and evaluation. Data were collected through observation, interviews, discussions, and documentation, then analyzed descriptively qualitatively. The results of the activity showed that participants gained an increased understanding of the importance of business development strategies, simple financial recording, and the use of digital media in expanding marketing reach. In addition, participants showed high enthusiasm during the activity and were committed to applying the material they had learned in managing their businesses. This activity demonstrates that participatory mentoring can improve the knowledge and motivation of MSMEs to develop their businesses more productively and sustainably. Therefore, ongoing collaboration between village governments, universities, and MSMEs is necessary to support the economic empowerment of rural communities.